PARTICULARS OF PROMOTING IN THE SOCIAL MEDIA - Cristian, MOROZAN; Mihaela, ASANDEI (Strategii Manageriale, 2014)
The classical promotional media, especially the television, have been often criticized for the contradictory effects that they have on the consumers. Compared to those, the Internet and social networks that support them represent an interactive environment, because consumers have more time and space to evaluate the products compared with the traditional seconds or tens of seconds of the TV spots or the few printed lines in newspapers. The promotion on the web and social media have an important role in consumers' informing, by providing the data they need for the purchasing decision, by providing feedback from others etc. For example, in the discussion groups and social networking sites, such products/services and software news are discussed and carefully evaluated by a permanent feedback from users, their responses being made posted on the internet.